Technological opportunities for the PV industry in Argentina: satellite and terrestrial developments - Valdivia Alcántara, Carlos; Canafoglia, Eliana (Frontiers in Energy Research, 2025)
Argentina possesses abundant quartz resources and a solid scientific legacy in nuclear and satellite technologies. However, the country lacks a developed value chain for producing solar-grade silicon. This paper aims to analyze Argentina’s current situation, identify existing capabilities, and assess the obstacles to creating a local silicon industry for photovoltaic applications. A qualitative research approach was used, based on document analysis and triangulation of national and international sources. The study identifies the relevant actors, policies and infrastructure relating to quartz mining, silicon purification and photovoltaic development. Results show that while Argentina has institutional knowledge and quartz reserves—especially in Córdoba and San Luis—it lacks purification facilities, specialized laboratories, and policy coordination. Key institutions like CNEA and INVAP possess technical know-how but are disconnected from productive sectors. The article concludes that Argentina’s integration into the global photovoltaic value chain depends on targeted policies, infrastructure development, and international cooperation. It recommends pilot purification plants, improved material testing capacity, and a national strategy for high-purity silicon.